2019
DOI: 10.1029/2018ja026248
|View full text |Cite
|
Sign up to set email alerts
|

Jensen‐Shannon Complexity and Permutation Entropy Analysis of Geomagnetic Auroral Currents

Abstract: In this study we determine whether auroral westward currents can be characterized by low-dimensional chaotic attractors through the use of the complexity-entropy methodology developed by Rosso et al. (2007, https://doi.org/10.1103/PhysRevLett.99.154102) and based on the permutation entropy developed by Bandt and Pompe (2002, https://doi.org/10.1103/PhysRevLett.88.174102). Our results indicate that geomagnetic auroral indices are indistinguishable from stochastic processes from time scales ranging from a few mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 54 publications
3
23
0
Order By: Relevance
“…These results suggest the persistence of an important stochastic component in the hourly AE index during both moderately and strongly disturbed periods, whereas Dst and ap become much more regular/organized during stronger disturbances. This corresponds to the higher variability of substorm field‐aligned currents (responsible for magnetic field perturbations in the auroral region) than the ring current, but it likely corresponds also to a higher stochasticity of AE than Dst or ap during higher geomagnetic activity—in agreement with recent results from Osmane et al (). But in this case, how to explain the good correlation between P* and Dst or ap entropies, if the intermediary auroral indices AE and AL are themselves significantly stochastic?…”
Section: Entropy Correlations Between Geomagnetic Indices and A Solarsupporting
confidence: 89%
See 2 more Smart Citations
“…These results suggest the persistence of an important stochastic component in the hourly AE index during both moderately and strongly disturbed periods, whereas Dst and ap become much more regular/organized during stronger disturbances. This corresponds to the higher variability of substorm field‐aligned currents (responsible for magnetic field perturbations in the auroral region) than the ring current, but it likely corresponds also to a higher stochasticity of AE than Dst or ap during higher geomagnetic activity—in agreement with recent results from Osmane et al (). But in this case, how to explain the good correlation between P* and Dst or ap entropies, if the intermediary auroral indices AE and AL are themselves significantly stochastic?…”
Section: Entropy Correlations Between Geomagnetic Indices and A Solarsupporting
confidence: 89%
“…It is also consistent with the somewhat lower SampEn(AE) during smaller Int(ap) and Int(AE) intervals in Figure 1 (bottom row): relatively quiet 10-day periods are simply less stochastic than a random succession of substorms and injections. A recent study has also shown that AE and AL are practically indistinguishable from stochastic processes in terms of hourly dynamical complexity 10.1029/2019JA027599 (Osmane et al, 2019). Apparently, AE mainly describes the directly driven, partly stochastic response of the magnetosphere to solar wind forcing, whereas higher organization arises in the delayed and entangled consequences occurring well within the inner magnetosphere-ionosphere system itself.…”
Section: Figure 2a Demonstrates Thatmentioning
confidence: 99%
See 1 more Smart Citation
“…To further verify the statistical robustness of the analysis, we confirmed that the studied data intervals satisfied the criteria N/d! > 10 and d!/(N − (d − 1)τ ) < 0.2 (Osmane et al 2019) for every value of τ . Figure 4 shows the values of H and C versus τ for the 1 s fluctuation amplitudes of the magnetic field magnitude and RTN components.…”
Section: Calculation Methodsmentioning
confidence: 94%
“…In other words, one can seek timescales upon which coherent structures/fluctuations/modes arise. In some instances, coherent modes are signatures of deterministic chaos (Maggs and Morales, 2013) or a reduction to the number of degrees of freedom (Osmane et al, 2019). Readers with little familiarity with these two information theoretic measures can consult the reviews of Riedl et al (2013) and Zanin et al (2012) or the pedestrian methodology section found in Osmane et al (2019).…”
Section: Creation Of Composite (Aggregate) Variables From the State Vmentioning
confidence: 99%